Muenke syndrome: Medical and surgical comorbidities and long‐term management. Issue 8 (20th May 2019) - Murali, Chaya N.; McDonald‐McGinn, Donna M.; Wenger, Tara Lynn; McDougall, Carey; Stroup, Bridget M.; Sheppard, Sarah E.; Taylor, Jesse; Bartlett, Scott P.; Bhoj, Elizabeth J.; Zackai, Elaine H.; Santani, Avni
Abstract: Muenke syndrome (MIM #602849), the most common syndromic craniosynostosis, results from the recurrent pathogenic p.P250R variant in FGFR3 . Affected patients exhibit wide phenotypic variability. Common features include coronal craniosynostosis, hearing loss, carpal and tarsal anomalies, and developmental/behavioral issues. Our study examined the phenotypic findings, medical management, and surgical outcomes in a cohort of 26 probands with Muenke syndrome identified at the Children's Hospital of Philadelphia. All probands had craniosynostosis; 69.7% had bicoronal synostosis only, or bicoronal and additional suture synostosis. Three male patients had autism spectrum disorder. Recurrent ear infections were the most common comorbidity, and myringotomy tube placement the most common extracranial surgical procedure. Most patients (76%) required only one fronto‐orbital advancement. de novo mutations were confirmed in 33% of the families in which proband and both parents were genetically tested, while in the remaining 66% one of the parents was a mutation carrier. In affected parents, 40% had craniosynostosis, including 71% of mothers and 13% of fathers. We additionally analyzed the medical resource utilization of probands with Muenke syndrome. To our knowledge, these data represent the first comprehensive examination of long‐term management in a large cohort of patients with Muenke syndrome. Our study adds valuable information regarding neuropsychiatric and medical comorbidities, and highlights findings in affected relatives.